Síntese de complexo polieletrolítico supramolecular κ-carragena-quitosana ancorado com Β-CD para sistema de liberação controlada do fármaco sulfadiazina de prata - Evangelista, Thamasia Fernanda de Sá (2020)
The search for controlled drug delivery mechanisms has been relevant in recent decades, with the aim of establishing more efficient therapeutic alternatives. In this work, a supramolecular polyelectrolytic complex (SPEC) between the biopolymers, κcarrageenan (CRG) chitosan (CS) functionalized with β-CD, in the stoichiometric ratio 4.25:1 obtained after determining the isoelectric point, was complexed to the sulfadiazine of silver (SDZ-Ag), a specific antibiotic for the treatment of burns and skin lesions. The samples were characterized by FTIR, DSC, TG, SEM and zeta potential techniques, which confirmed the formation of the polymeric complex. In this work, SDZ-Ag was used as a model drug and the association with supramolecular polyelectrolytic complexes was also studied by computational molecular modeling, using a semi-empirical method. The DRS and MET analyzes showed that the drug's Ag+ ions were reduced to different average sizes (12, 35 and 53 nm) through silver metallic non-structures. In vitro tests using Gram-positive strains: Staphylococcus aureus (ATCC 25923), Enterococcus durans/hirae (SS1225 / IAL 03/10) and Gram-negative: Klebsiella pneumoniae (ATCC 700603), Escherichia coli (ATCC 25922) and Enterobacter aerogenes (ATCC 13048), were used to evaluate the antimicrobial and kinetic profile of SPEC, observing drug release in 24 hours and pure SDZ in 5.5 hours. Finally, this work shows that the CDchitosan/carrageenan supramolecular polyelectrolyte complexes have an expressive potential to be applied as a polymer-based system for controlled drug release.